Characteristics of Doppler Effect in Satellite Telecommunication Systems - Stecevicius, R. (Elektronika ir Elektrotechnika, 1997)
The more exact mathematical modelling way of relative velocity is proposed and digitally investigated in this issue, using three dimensional geometry of satellite systems. Slope orbit parameters, Earth rotation and consumer’s geographic co-ordinates are taken into account. Some restrictive factors of information transmission considering telecommunication systems without compensation of Doppler effect are briefly discussed here.